Gibbs' rational reconstruction of thermodynamics according to the heuristic tradition of Descartes' analytical method - Jojomar Lucena; Cássio Costa Laranjeiras; José Raimundo Novaes Chiappin (Revista Brasileira de Ensino de Física)
Abstract Many rational aspects of some fields of physics, including those related to the process of discovery, may be better understood using methodological tools typical of the philosophical analysis of science. Throughout this paper we shall use the heuristic tradition of Descartes' analytical (or discovery) method for a rational reconstruction of Gibbs' thermodynamics, or thermodynamics of potentials, seeking to emphasize the potentialities of the representational character of science. Our contention is that Descartes's method of discovery illuminates the intellectual itinerary of the construction of the thermodynamics of potentials.